Durasi Penggunaan Media Sosial Dan Insomnia Pada Remaja - I Gede Purnawinadi; Stela Salii (Fakultas Keperawatan, Universitas Klabat, 2020)
Rest and sleep are physiological needs that must be met by every teenager. The inability of teenagers in managing time to use social media will have an impact on irregular sleep patterns so that the occurrence of insomnia. This study aims to determine the relationship of the duration of social media use with insomnia in teenager at Advent Klabat Manado High School. The method used in this study is an analytic survey with cross sectional approach. Data of 155 respondents were collected using a questionnaire through a total sampling technique. Data were analyzed bivariately using the spearman correlation test. The results of this study descriptively that there were 91 respondents (58.7%) dominant with a moderate duration of social media use (3-4 hours a day) and 99 respondents (56.8%) had moderate insomnia. There is a strong and positive correlation between the duration of social media use and the incidence of insomnia in adolescents at Manado Klabat Advent High School (p value = 0.00 <0.05, with r = 0.739). It is expected that teenagers to reduce the use of social media and replace with other useful activities, for researchers can then analyze specifically the types of social media that are often used by teenagers. Keywords: duration, use of social media, insomnia, teenagers